Beaver: Nature's ecosystem engineers. (27th November 2020) - Brazier, Richard E.; Puttock, Alan; Graham, Hugh A.; Auster, Roger E.; Davies, Kye H.; Brown, Chryssa M. L.
Abstract: Beavers have the ability to modify ecosystems profoundly to meet their ecological needs, with significant associated hydrological, geomorphological, ecological, and societal impacts. To bring together understanding of the role that beavers may play in the management of water resources, freshwater, and terrestrial ecosystems, this article reviews the state‐of‐the‐art scientific understanding of the beaver as the quintessential ecosystem engineer. This review has a European focus but examines key research considering both Castor fiber —the Eurasian beaver and Castor canadensis —its North American counterpart. In recent decades species reintroductions across Europe, concurrent with natural expansion of refugia populations has led to the return of C. fiber to much of its European range with recent reviews estimating that the C. fiber population in Europe numbers over 1.5 million individuals. As such, there is an increasing need for understanding of the impacts of beaver in intensively populated and managed, contemporary European landscapes. This review summarizes how beaver impact: (a) ecosystem structure and geomorphology, (b) hydrology and water resources, (c) water quality, (d) freshwater ecology, and (e) humans and society. It concludes by examining future considerations that may need to be resolved as beavers further expand in the northern hemisphere with an emphasis upon the ecosystem services that they can provide and the associated management that will be necessary to maximize the benefits and minimize conflicts. This article is categorized under: Water and Life > Nature of Freshwater Ecosystems Abstract : This article reviews the state‐of‐the‐art scientific understanding of the beaver as an ecosystem engineer. It summarizes how beaver impact: (a) ecosystem structure and geomorphology, (b) hydrology and water resources, (c) water quality, (d) freshwater ecology, and (e) humans and society.